The human development index as isoelastic GDP: Evidence from China and Pakistan - Gordon Bechtel (Economies, 2018)
Gross domestic product (GDP) is shown to possess three new desiderata. First, GDP is almost perfectly correlated over time with the first principal component of its three classical indicators. Second, this principal component is in a class of weighted indexes ancillary to GDP. Each ancillary index informs policy as to allocation of resources over the three GDP indicators. Third, a country-specific power of GDP almost perfectly predicts the United Nation's Human Development Index (HDI). These findings are brought by principal components and regression analyses of time series supplied by the World Bank and the United Nations. Axiomatic HDI computation is carried out without survey sampling, probabilistic inference, significance testing, or even HDI data.
Keywords: C22; C38; C43; E21; E51; F50; F62; F63; I31; 330; societal data theory; country specificity; internal consistency of GDP indicators; latent population distributions; latent 2-level principal-components analysis; Nt-weighted versus weighted GDP indicators